Analisis Kinerja Keuangan Perusahaan dengan Menggunakan Metode Economic Value Added (EVA) - sri dwi ningsih; Tanti Muslimah (JAMIN : Jurnal Aplikasi Manajemen dan Inovasi Bisnis, 2020)
This research was conducted to analyze the financial performance of property and real estate sector companies listed on the Indonesia Stock Exchange (BEI) using the Economic Value Added (EVA) method.This research is a quantitative research, where the data source is secondary data in the form of company annual financial reports for the period 2016 to 2018. The population of this study is a property and real estate sector company listed on the IDX, the sample of this study is five companies with sampling using the purposive sampling method. , data collection is done through documentation and literature study, then the analysis technique uses the EVA method with the calculation of NOPAT, Invested Capital, WACC and CC.The results of this study indicate that by using the EVA method, it is known that four companies produce a positive EVA value or EVA> 0 means that the company can generate added value, namely PT. Bumi Serpong Damai Tbk, PT. Summarecone Agung Tbk, PT. PP Properti Tbk, PT. Lippo Karawaci Tbk, meanwhile one company produces a negative EVA value or EVA <0 means that the company has not been able to generate added economic value, namely PT. Pakuwon Jati Tbk.